Clones within Clones: Cosmology and Esthetics and Polynesian Crop Selection - Meilleur, Brien A. (Anthropologica, 2022)
Polynesians living on tropical and temperate high islands in the Pacific traditionally maintained large inventories of cultivars (cultivated varieties) in vegetatively propagated crop species or cultigens. This intraspecific or "within species" diversification has usually been explained in ecological functional terms, with cultivar selections seen as human adaptive responses to variation in natural and agricultural ecosystems. But recent research reveals little genetic basis to the Polynesian polyvarietal phenomenon and further suggests that functional equivalency existed among some cultivars in agricultural contexts. Hawaiian polyvarietal phenomena are described and crop folk classification is outlined. Utility and perceptual distinctiveness are explored along with indigenous concepts of cosmology and esthetics as criteria that in combination may better account for the large inventories of crop cultivars in Hawaii and Polynesia.